The Clothes Off Our Back: A History of ACTWU 459 - Black, Errol (Labour / Le Travail, 1997)
The article reviews the book,"The Clothes Off Our Back: A History of ACTWU 459," by Debra Lindsay.
Keywords: AMALGAMATED Clothing & Textile Workers Union; BOOKS – Reviews; CLOTHES off Our Back: A History of ACTWU 459; The (Book); LINDSAY; Debra; Nonfiction